2014
DOI: 10.1073/pnas.1401876111
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics induce redox-related physiological alterations as part of their lethality

Abstract: Deeper understanding of antibiotic-induced physiological responses is critical to identifying means for enhancing our current antibiotic arsenal. Bactericidal antibiotics with diverse targets have been hypothesized to kill bacteria, in part by inducing production of damaging reactive species. This notion has been supported by many groups but has been challenged recently. Here we robustly test the hypothesis using biochemical, enzymatic, and biophysical assays along with genetic and phenotypic experiments. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

47
725
3
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 737 publications
(787 citation statements)
references
References 111 publications
47
725
3
12
Order By: Relevance
“…A subsequent paper by Dwyer et al (27) provided further evidence that ROS production was a typical consequence of the cellular disruption caused by antibiotics, and thus could enhance the lethality of antibiotics beyond their primary modes of action. The results presented here resonate with all four of these studies in that the lethal insults we studied (T6SS effectors, P1vir phage, and polymyxin B) induced ROS production but cell killing could occur by nonoxidative (cell wall hydrolysis, phage replication, and envelope disruption, respectively) as well as oxidative mechanisms depending upon the insult.…”
Section: Significancementioning
confidence: 99%
See 3 more Smart Citations
“…A subsequent paper by Dwyer et al (27) provided further evidence that ROS production was a typical consequence of the cellular disruption caused by antibiotics, and thus could enhance the lethality of antibiotics beyond their primary modes of action. The results presented here resonate with all four of these studies in that the lethal insults we studied (T6SS effectors, P1vir phage, and polymyxin B) induced ROS production but cell killing could occur by nonoxidative (cell wall hydrolysis, phage replication, and envelope disruption, respectively) as well as oxidative mechanisms depending upon the insult.…”
Section: Significancementioning
confidence: 99%
“…Previous reports suggested that the expression of soxS could be up-regulated by antibiotics (16,27), volatile organic compounds (39), and hydrogen peroxide (40). Interestingly, all of these compounds can be produced by various bacterial species.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Under sustained exposure to norfloxacin, mutation rates revealed by reporter constructs can be elevated 2-9 times (18,23). Norfloxacin is also thought to elevate intracellular reactive oxygen species (ROS) levels (24,25), which may further increase the rate of genomic mutation and the subsequent rate of acquisition of multidrug resistance (23,26).…”
mentioning
confidence: 99%